PENGGUNAAN KONJUNGSI DALAM KORAN HARIAN MEDIA INDONESIA - Anah Mutaslimah; Mangatur Sinaga; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research aims to know the percentage of the use of coordinative conjunction appropriate and inappropriate, subordinatif conjunction appropriate and inappropriate, correlative conjunction appropriate and inappropriate, antarkalimat conjunction appropriate and inappropriate, and antarparagraf conjunction appropriate and inappropriate in the daily newspaper Media Indonesia. This research was used qualitative research methods. The object of this research that quotes a sentence in the daily newspaper Media Indonesia, which used the coordinative conjunction, subordinatif conjunction, correlative conjunction, antarkalimat conjunction, and antarparagraf conjunction. The data collection was obtained by using a technique of documentation. The result of research was percentage the use of coordinative conjunction appropriate and inappropriate, subordinatif conjunction appropriate and inappropriate, correlative conjunction appropriate and inappropriate, antarkalimat conjunction appropriate and inappropriate, and antarparagraf conjunction appropriate and inappropriate in the daily newspaper Media Indonesia. Based on the data analysis found that the use of coordinative conjunction are 84,3% appropriate and 15,7% inappropriate. The use of subordinative conjunction are 92,6% appropriate and 7,4% inappropriate. The use of correlative conjunction are 30% appropriate and 70% inappropriate. The use of antarkalimat conjunction are 66,7% appropriate and 33,3% inappropriate. The use of antarparagraf conjunction are 40% appropriate and 60% inappropriate. The total overall were 86,3% use of conjunction with right and 13,7% use of conjunction not right.Keys words: conjunction, coordinative, subordinative, correlative, Media Indonesia